The Case Against Christianity - Martin, Michael (Philadelphia Temple University Press, 1991)
Presenting a systematic philosophical critique of the tenets of Christianity, this book examines the semantic and epistemological bases of religious claims and beliefs. Beginning with a comparison and evaluation of the Apostles' Creed, it discusses the pr
Keywords: Christianity -- Controversial literature. Christianity. Christendom